Macroeconomic Policy Making, Exchange Rate Adjustment and Current Account Imbalances in Emerging Markets - Pablo Duarte; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2014)
Since a series of crisis events after 2007, the discussion about the adjustment channels of current account imbalances has been revived. We discuss the effectiveness of exchange rates versus macroeconomic policies to rebalance current accounts for a set of 86 mainly emerging market economies. We find that nominal exchange rates are not a sufficient adjustment channel for (unsustainable) current account positions. Instead, depending on the region, monetary and/or fiscal policies are the main determinants of current accounts. For East Asia and the oil exporting countries sterilization policies, i.e. relatively tight monetary policies, are the main determinants. In contrast the main driving forces for emerging and southern Europe are fiscal policy stances. Only for the Latin American countries the exchange rate seems to play a significant role.
Keywords: F43; E42; F31; 330; global imbalances; intra-european imbalances; exchange rate adjustment; monetary policy; fiscal policy